Artificial Intelligence (AI) Based Marketing: Optimization in Changing Consumer Behavior Through E-Commerce Platforms - Tjahyono, Rudi; Kusuma Wijaya, Dewa; Hardiningsih, Pancawati (Paradoks : Jurnal Ilmu Ekonomi, 2025)
The increasing use of artificial intelligence (AI) in digital marketing has revolutionized how e-commerce businesses interact with consumers. AI enables content personalization, predictive analysis of consumer needs, and automation of various aspects of marketing. However, the extent to which this technology influences consumer behaviour still needs further research. This study examines the impact of AI-based marketing on consumer behaviour, specifically in purchasing decisions, customer loyalty, and brand engagement on e-commerce platforms. Using AI-based personalization techniques and AI-powered chatbots, e-commerce platforms such as Shopee and Tokopedia offer customized experiences to increase consumer satisfaction and long-term loyalty. The analysis was conducted to determine how AI-based marketing strategies consisting of content personalization and chatbot interactions can influence consumer behaviour and contribute to the development of effective marketing strategies in the e-commerce industry.